Adaptasi Masyarakat sebagai Wujud Ketangguhan Pasca Bencana: Studi Kasus Desa Pombewe Dan Jono Oge - By Bethania Yunike Fridianti; Wiyatiningsih Wiyatiningsih; Paulus Bawole (Jurnal Kajian dan Penelitian Umum, 2026)
Jono Oge Village, Sigi Biromaru Regency, Central Sulawesi, has been designated a liquefaction-prone area with a high risk level. Following the 2018 liquefaction disaster, the government relocated residents to permanent housing (huntap) as a mitigation measure. This policy created a dynamic in the settlements due to differences in housing choices and limited community participation in the planning process. Some residents chose to return to their original locations and build housing independently despite ongoing disaster risks, while others remained in the provided permanent housing. These differing choices are not merely physical or spatial in nature, but also reflect the complex social, cultural, and economic ties that communities hold toward their former places of residence. This research uses a qualitative approach with a case study method, conducted in the permanent housing complex of Pombewe and the independent housing complex of Jono Oge, to analyze the forms of community adaptation and resilience after the disaster. The research's novelty lies in identifying spatial housing adjustment mechanisms as a social, economic, and cultural adaptation strategy to maintain post-disaster life.